Contestation and resource bargaining in Zimbabwe: The minerals sector - Richard Saunders (United Nations Research Institute for Social Development (UNRISD), 2017)
This paper explores the emergence and evolution of social contestation over mineral resources in Zimbabwe through three decades and successive models of state engagement around extractives, revenue mobilization and development planning. It investigates patterns of contestation and outcomes around core issues in the sector, including the mining fiscal regime, the participation of small-scale mining and communities, and the management of the labour market. In exploring the evolving role of stakeholders and constituencies, the paper weighs the origins and effectiveness of different resource mobilization models in terms of the space they provide for meaningful and effective contestation. If gains have been realized under a model, the study asks which constituencies have gained, proposing which vision of development, and under what circumstances of relational power among stakeholders. Similarly, the question of who may have lost - in rhetoric and in practice - is also posed. More broadly, the paper seeks to understand the dynamics of changing forms of state-citizen, state-market and state-donor engagement. Policy practices have been successively dominated and primarily shaped by an elite-driven consensus of political and industry actors, as evidenced by historical patterns of resource mobilization and social development linked to the mining sector. Policy making has been disproportionately focused on the accommodation of "market imperatives" and industrial viability, and has been resistant to meaningful, transparent and sustained forms of social inclusion and redistribution. Recurrent macroeconomic vulnerabilities have resulted in strong donor influence, and have strengthened the capacity of foreign capital to obstruct policy implementation. The consequence has been a persistent and evolving weakness in the mobilization of fiscal resources from the minerals sector, representing a lost opportunity for mining's contribution to social development.
Additional information: Prepared for the UNRISD project on Politics of Domestic Resource Mobilization for Social Development
Keywords: 330